Bibliometric Analysis of the Development of Local Culture-Based Elementary Social Studies E-Modules for PGSD Students - Guslinda; Suarman; Sumarno; Putra, Zetra Hainul (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
Understanding and introduction to local culture is important for prospective elementary school teachers through the development of social studies learning e-modules. The purpose of this study is to analyze the development of social studies learning e-modules based on local culture, by analyzing articles published in 2018-2022. The analysis was conducted using bibliometric analysis supported by VOSviewer, Publish or Perish (POP). There are 300 articles from the database taken from Harzing's Publish or Perish, Google Scholar related to this research. Furthermore, all articles were screened and 35 articles were obtained that matched the keyword